Updated results from MONALEESA-2, a phase III trial of first-line ribociclib plus letrozole versus placebo plus letrozole in hormone receptor-positive, HER2-negative advanced breast cancer. (27th April 2018) - Hortobagyi, G N; Stemmer, S M; Burris, H A; Yap, Y S; Sonke, G S; Paluch-Shimon, S; Campone, M; Petrakova, K; Blackwell, K L; Winer, E P; Janni, W; Verma, S; et al.
Abstract: Background: The phase III MONALEESA-2 study demonstrated significantly prolonged progression-free survival (PFS) and a manageable toxicity profile for first-line ribociclib plus letrozole versus placebo plus letrozole in patients with hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2–) advanced breast cancer. Here, we report updated efficacy and safety data, together with exploratory biomarker analyses, from the MONALEESA-2 study. Patients and methods: A total of 668 postmenopausal women with HR+, HER2– recurrent/metastatic breast cancer were randomized (1 : 1; stratified by presence/absence of liver and/or lung metastases) to ribociclib (600 mg/day; 3-weeks-on/1-week-off; 28-day treatment cycles) plus letrozole (2.5 mg/day; continuous) or placebo plus letrozole. The primary end point was locally assessed PFS. The key secondary end point was overall survival (OS). Other secondary end points included overall response rate (ORR) and safety. Biomarker analysis was an exploratory end point. Results: At the time of the second interim analysis, the median duration of follow-up was 26.4 months. Median PFS was 25.3 months [95% confidence interval (CI) 23.0–30.3] for ribociclib plus letrozole and 16.0 months (95% CI 13.4–18.2) for placebo plus letrozole (hazard ratio 0.568; 95% CI 0.457–0.704; log-rank P  =   9.63 × 10 −8 ). Ribociclib treatment benefit was maintained irrespective of PIK3CA or TP53 mutation status, total Rb, Ki67, or p16 protein expression, and CDKN2A, CCND1, or ESR1 mRNA levels. Ribociclib benefit was more pronounced in patients with wild-type versus altered receptor tyrosine kinase genes. OS data remain immature, with 116 deaths observed; 50 in the ribociclib arm and 66 in the placebo arm (hazard ratio 0.746; 95% CI 0.517–1.078). The ORR was 42.5% versus 28.7% for all patients treated with ribociclib plus letrozole versus placebo plus letrozole, respectively, and 54.5% versus 38.8%, respectively, for patients with measurable disease. Safety results, after a further 11.1 months of follow-up, were comparable with those reported at the first analysis, with no new or unexpected toxicities observed, and no evidence of cumulative toxicity. Conclusions: The improved efficacy outcomes and manageable tolerability observed with first-line ribociclib plus letrozole are maintained with longer follow-up, relative to letrozole monotherapy. Clinical trials number: NCT01958021